Psychometric properties of the Plutchik suicide risk scale in a sample of young Mexicans deprived of freedom - Santana-Campas, Marco Antonio (2018)
The objective was to report the psychometric properties of the Plutchik Suicide Risk Scale in prison sample. Method, non-experimental and correlational quantitative research. Sample: 395 young people deprived of freedom, 84.1% men and 15.9% women, the age range was 15 to 29 years. It was taken from five penitentiary institutions in Jalisco, Mexico. Instruments: Plutchik Suicide Risk Scale and Beck’s Hopelessness Scale. Results, the Cronbach’s alpha of the scale was .745, the confirmatory factorial showed an optimal fit, the approach’s error average square root (RMSEA <.05) was .05, the chi-square ratio on the degrees of freedom (CMIN/DF <3) was 1.99 and the goodness of fit index (GFI> .9) was .949. This scale demonstrated adequate psychometric properties, which is why it is an ideal instrument to identify the risk of suicide.